Understanding The Relationship Between Competitive Intelligence and Strategic Management of Universities: A Critical Review - Rahmi, Nur; Ishak, Parmin; Oli'i, Nurhayati (Pusat Penerbitan dan Publikasi Ilmiah Fakultas Ekonomi, Universitas Muslim Indonesia, 2020)
The purpose of this paper is to provide references for research on university strategic practice and intellectual intelligence. This research also aims at the current university strategic management situation, starting from the analysis of the relationship between competitive intelligence and university strategic management, discussing strategic analysis and strategic selection in the university's strategic management process. Strategic selection, implementation, and evaluation in four stages of interaction and relation to competitive intelligence. The method used in this study is a critical review of the implementation of strategic management at universities in Indonesia by taking several references from journals, magazines, news, and regulations of the Educational Institution. It was concluded that the strategic management and competitive intelligence on colleges and universities have the interaction and integration relationship, both jointly build conclusions competitive on profit universities, to provide a reference for the study and practice of strategic management of universities and jobs competitive intelligence university.